Nutritional Support for a Child With Juvenile Myelomonocytic Leukaemia at Various Stages of Antineoplastic Therapy: A Clinical Case - Mariam S. Shamsutdinova; Yulia A. Alymova; Andrey Yu. Vashura (Вопросы современной педиатрии, 2019)
Background. Juvenile myelomonocytic leukaemia is a malignant disease with clonal impairment of haematopoiesis, characterized by excessive proliferation of monocytic and granulocytic sprout. Currently, the only way to cure it is hematopoietic stem cell transplantation. Vigorous treatment is accompanied by the development of a large number of complications, including nutritional ones. Nutritional support for these patients is fraught with many difficulties due to the treatment characteristics, patient’s condition, and complications of therapy. Description of a Clinical Case. A child diagnosed with juvenile myelomonocytic leukaemia, 1 year and 11 months old, received antineoplastic therapy — chemotherapy and bone marrow transplantation. In the course of treatment and after it, severe complications developed, which required various types of nutritional support, depending on the clinical situation. It is illustrated how important timely nutritional support is and how long and difficult nutritional disorders can proceed in these children even after termination of the main therapy. Conclusion. Preventive nutritional support with infant formulas is advisable for children with oncological diseases prior to treatment even with normal nutritional indicators. With the potential long-term impossibility of adequate alimentation per os, it is advisable to consider the placement of a gastrostomy tube for enteral nutrition since problems with appetite can be very long.